If I only knew - Jones, Tom; Horn, Trevor; White Rhino Music (United States : White Rhino Music, 1994)
Contains three versions of the single.
Cold Stop Version (3:45) -- LP Version (4:06) -- Fade Out Version (3:40).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Popular music; Country music